A European unemployment benefits scheme: lessons from Canada - Wood, Donna (Brussels, 2017)
"In many federal political systems, responsibility for unemployment has a multi-tiered architecture, with competence for key elements such as unemployment insurance, social assistance, and the public employment service, dispersed across different orders of government.